Prevalence and Risks Factors of Prehypertension in Africa: A Systematic Review - Koussoh Simone Malik; Kassi Anicet Adoubi; Jérôme Kouame; Madikiny Coulibaly; Marie-Laure Tiade; Serge Oga; Michèle Ake; Odile Ake; Luc Kouadio (Ubiquity Press, 2022)
Background: Hypertension is one of the major factors for high mortality of adults in Africa. However, complications occur at lower values than those previously classified as hypertension. Thus, prehypertension is considered as a new category of hypertension and a major risk factor for developing clinical hypertension relative to those with normotension, it has been linked with increased future risk of hypertension as well as cardiovascular diseases. Objectives: The objective of this review was to determine prevalence of prehypertension and describe the associated factors of prehypertension in Africa during the past 10 years. Methods: We did a systematic review using the databases PubMed/Medline, and search engine google scholar. We selected sources of publications and conducted an analysis of articles. Keywords in English were: prehypertension, high normal blood pressure, high blood pressure, elevated blood pressure, Africa. Keywords in french were: préhypertension artérielle, préhypertension, pression artérielle normale haute, pression artérielle normale, Afrique. Mesh terms were: Prehypertension, Africa. Results: Twenty-seven articles were selected. Prevalence of prehypertension ranged from 2.5% to 34% in children and adolescents. In adults, prevalence varied from 32.9% to 56.8%. Several factors were associated with prehypertension in Africa. These factors included: age; sex; lifestyle such as smoking, alcohol consumption, low physical activity, overweight and obesity. There were also cardiometabolic factors and few others factors which were associated with prehypertension. Conclusion: This review allowed us to observe that the prevalence of prehypertension was variable according to age of the population and prehypertension is associated with several factors.